Front Cover: Simple Plug‐In Synthetic Step for the Synthesis of (−)‐Camphor from Renewable Starting Materials (ChemBioChem 20/2021). (28th June 2021) - Calderini, Elia; Drienovská, Ivana; Myrtollari, Kamela; Pressnig, Michaela; Sieber, Volker; Schwab, Helmut; Hofer, Michael; Kourist, Robert
Abstract : (−)‐Camphor can occur naturally as a constituent of essential oils of several plants, including Cinnamomum camphora, or it can be obtained chemically from optically pure α‐pinene, which itself must be isolated from plants. Camphor is well known for its characteristic pungent odor and health benefits. While (+)‐camphor can be isolated from various natural sources, (−)‐camphor is more difficult to obtain. In our work, we demonstrate facile enantioselective kinetic resolution of renewable isobornyl esters for the synthesis of the valuable (−)‐camphor. More information can be found in the Communication by M. Hofer, R. Kourist et al.